Impact of 2 days of staging at 2500–4300 m on sleep quality and quantity following subsequent exposure to 4300 m - Janet E. Staab (Wiley, 2021)
Abstract The impact of 2 days of staging at 2500–4300 m on sleep quality and quantity following subsequent exposure to 4300 m was determined. Forty‐eight unacclimatized men and women were randomly assigned to stage for 2 days at one of four altitudes (2500, 3000, 3500, or 4300 m) prior to assessment on the summit of Pikes Peak (4300 m) for 2 days. Volunteers slept for one night at sea level (SL), two nights at respective staging altitudes, and two nights at Pikes Peak. Each wore a pulse oximeter to measure sleep arterial oxygen saturation (sSpO2, %) and number of desaturations (DeSHr, events/hr) and a wrist motion detector to estimate sleep awakenings (Awak, awakes/hr) and sleep efficiency (Eff, %). Acute mountain sickness (AMS) was assessed using the Environmental Symptoms Questionnaire and daytime SpO2 was assessed after AMS measurements. The mean of all variables for both staging days (STG) and Pikes Peak days (PP) was calculated. The sSpO2 and daytime SpO2 decreased (p < 0.05) from SL during STG in all groups in a dose‐dependent manner. During STG, DeSHr were higher (p < 0.05), Eff was lower (p < 0.05), and AMS symptoms were higher (p < 0.05) in the 3500 and 4300 m groups compared to the 2500 and 3000 m groups while Awak did not differ (p > 0.05) between groups. At PP, the sSpO2, DeSHr, Awak, and Eff were similar among all groups but the 2500 m group had greater AMS symptoms (p < 0.05) than the other groups. Two days of staging at 2500–4300 m induced a similar degree of sleep acclimatization during subsequent ascent to 4300 m but the 2500 m group was not protected against AMS at 4300 m.